THE CRIME OF AGGRAVATED THEFT COMMITTED CONTINUOUSLY (A CASE STUDY OF DECISION NUMBER 942/PID.B/2025/PN LBP) - Khairul Sitepu; Tri Reni Novita (CV. Barokah Publsiher, 2026)
The research findings indicate that the legal provisions for the crime of aggravated theft committed continuously are stipulated in Articles 362, 363, and 64 of the Criminal Code. The Public Prosecutor's indictment against the perpetrator of aggravated theft committed continuously in Decision Number 942/Pid.B/2025/PN Lbp has fulfilled the formal requirements, while the material requirements have partially not been met. The judge's legal considerations regarding the elements of the crime of theft, aggravating circumstances, and continued acts in Decision Number 942/Pid.B/2025/PN Lbp are appropriate, namely, the legal considerations that conclude that the elements have been fulfilled based on the evidence of witness testimony, the defendant's statement, and indicative evidence are appropriate in accordance with Article 184 of the Criminal Procedure Code.